2021
DOI: 10.1093/eurheartj/ehab724.2070
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban for treatment of embolic stroke of undetermined source (ATTICUS) randomized trial – update of patient characteristics and study timeline after interim analysis

Abstract: Background Secondary prevention after embolic stroke of undetermined source (ESUS) has not yet been established. ESUS is associated with high risk of recurrent ischemic stroke and clinically silent ischemic lesions. Secondary prevention with aspirin is the current standard therapy in ESUS patients, despite high prevalence of occult atrial fibrillation (AF). Purpose To determine whether the direct oral factor Xa inhibitor apix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Nevertheless, final details are still lacking at the time of writing this guideline. 133 Another study, ARCADIA (AtRial Cardiopathy and Antithrombotic Drugs In Prevention After Cryptogenic Stroke, NCT03192215) is now randomising ESUS patients with atrial cardiomyopathy (P-wave terminal force >5000 µV × ms in ECG lead V 1 , serum NT-proBNP > 250 pg/mL and LA diameter index ⩾3 cm/m 2 on echocardiogram) for treatment with apixaban or aspirin. The primary efficacy outcome is recurrent stroke and primary safety outcomes are symptomatic intracranial haemorrhage or non-intracranial major haemorrhages.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, final details are still lacking at the time of writing this guideline. 133 Another study, ARCADIA (AtRial Cardiopathy and Antithrombotic Drugs In Prevention After Cryptogenic Stroke, NCT03192215) is now randomising ESUS patients with atrial cardiomyopathy (P-wave terminal force >5000 µV × ms in ECG lead V 1 , serum NT-proBNP > 250 pg/mL and LA diameter index ⩾3 cm/m 2 on echocardiogram) for treatment with apixaban or aspirin. The primary efficacy outcome is recurrent stroke and primary safety outcomes are symptomatic intracranial haemorrhage or non-intracranial major haemorrhages.…”
Section: Resultsmentioning
confidence: 99%
“…To date, 23% of the study patients have developed AF during follow-up. 19 Hence, further assessment of predictors of AF in the ESUS population is warranted and is the basis for the ongoing randomized clinical trial ARCADIA (NCT03192215).…”
Section: Discussionmentioning
confidence: 99%
“…A secondary analysis of the NAVIGATE ESUS trial showed that left atrial diameter and premature atrial contraction frequency predicted subsequent clinical AF. The ATTICUS study, which stopped after the interim analysis owing to futility, looked at an ESUS population with a high risk profile for cardiac thromboembolism (ie, left atrium larger than 45 mm, spontaneous echo contrast in left atrium appendage, left atrium appendage flow velocity 0.2 cm/s or greater, atrial high-rate episodes, CHA2DS2-Vasc [congestive heart failure, hypertension, age 75 years and older, diabetes, stroke or transient ischemic attack, vascular disease, age 65-74 years, and sex category] score 4 or greater, and PFO). To date, 23% of the study patients have developed AF during follow-up .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…there are currently no guidelines for anti-coagulation use for ischemic stroke patients who are found to have atrial cardiopathy ( 37 , 38 ). The AtRial Cardiopathy and Antithrombotic Drugs In Prevention After Cryptogenic Stroke (ARCADIA) trial ( 8 ) and the Apixaban for Treatment of Embolic Stroke of Undetermined Source (ATTICUS) trial ( 39 , 40 ) are specifically randomizing patients with biomarker driven atrial cardiopathy (though different criteria than our study) to anticoagulation vs. antiplatelet therapy and may help answer some of these questions. Atrial cardiopathy may increase subclinical risk of embolic stroke, and with the addition of the findings of this study that risk may be marked by CMB ( 41 ).…”
Section: Discussionmentioning
confidence: 99%